Brand-to-generic levetiracetam switch in patients with epilepsy in a routine clinical setting. (May 2017) - Markoula, Sofia; Chatzistefanidis, Dimitrios; Gatzonis, Stylianos; Siatouni, Anna; Siarava, Eleftheria; Verentzioti, Anastasia; Kyritsis, Athanassios P; Patsalos, Philip N.
Highlights: Generic antiepileptic drugs (AEDs) are widely prescribed. Patients and physicians have concerns that they may cause therapeutic failure. Clinical practice data show that generic and brand levetiracetam are bioequivalent. Seizure frequency/adverse events were not affected upon switching to the generic. Abstract: Purpose: The therapeutic equivalence of generic and brand antiepileptic drugs, based on studies performed on healthy volunteers, has been questioned. We compare, in a routine clinical setting, brand versus generic levetiracetam (LEV) bioequivalence in patients with epilepsy and also the clinical efficacy and tolerability of the substitution. Methods: A prospective, open-label, non-randomized, steady-state, multiple-dose, bioequivalence study was conducted in 12 patients with epilepsy (5 females), with a mean age of 38.4 ± 16.2 years. Patients treated with the brand LEV (Keppra; UCB Pharma) were closely followed for a four-week period and subsequently switched to a generic LEV (Pharmaten) and followed for another four-week period. Blood samples were collected at the end of each 4-week period, during a dose interval for each formulation, for LEV concentration measurements by liquid chromatography mass spectrometry. Steady-state area under the curve (AUC) and peak plasma concentration (Cmax) data were subjected to conventional average bioequivalence analysis. Secondary clinical outcomes, including seizure frequency and adverse events, were recorded. Results: Patients had epilepsy for a mean period of 14.1 ± 10.6 years and the mean daily LEV dose was 2583.3 ± 763.7 mg. The mean AUC ± SD and Cmax ± SD was 288.4 ± 86.3 (mg/L) h and 37.8 ± 10.4 mg/L respectively for brand LEV and 319.2 ± 104.7 (mg/L) h and 41.6 ± 12.3 mg/L respectively for the generic LEV. Statistic analysis showed no statistical significant difference in bioequivalence. Also, no change in seizures frequency and/or adverse events was recorded. Conclusions: In our clinical setting, generic LEV was determined to be bioequivalent to brand LEV. Furthermore, seizures frequency or/and adverse events were not affected upon switching from brand to generic LEV.